PLANKTON OF CALICUT INSHORE WATERS AND ITS RELATIONSHIP WITH COASTAL PELAGIC FISHERIES - Mukundan, C (Indian Journal of Fisheries, 2011)
Studies on the inshore plankton of Calicut waters and on the related hydrologicalfeatuies have been made in earlier years, and there have been attempts, ingeneral terms or specifically, at correlating these with the fisheries of the area. FromHomell and Nayudu (1924) who suggested that the oil sardine might be cominginto the inshore waters to feed on the plankton there, various workers have followedthis view. Particular mention may be made, in this regard, of the observations ofChidambaram and Menon (1945) who arrived at a positive correlation between theplankton and the pelagic fisheries of this area during the post-monsoon period; ofGeorge (1953) who demarcated the inshore plankton as "edible" and "non-edible"from the point of view offish food and marked the fact that the fishery season alongthe coast coincided with the period of abundance of "edible plankton", suggestingclose relationship between the two; of Subrahmanyan (1959) who discussed therelationship of plankton production with fluctuations of oil sardine and mackerellandings on a month-to-month basis, finding broad correlation between standingcrop of the plankton and total quantity of fish landed.